Philosophy of Religion in Spanish Language. Comparison between two "hermeneutic Moments" - Santasilia, Stefano ('Ilu. Revista de Ciencias de las Religiones, 2025)
This article aims to offer a general reflection on the philosophy of religion in the Spanish language, with particular attention to its aspects and development in the 20th century. After a general introduction, which attempts to provide specific information regarding the presence of the philosophy of religion in the Spanish and Latin American cultural landscape, we will move on to a comparison between the thought of two authors who can be considered emblematic of the development of the discipline in the Spanish language. The thought of both authors will be taken into consideration to show how the philosophy of religion is conceived from an abandonment of the dimension of demonstrative reason in favor of the assumption of a hermeneutic perspective. It is precisely this perspective, oriented in a symbolic key, that allows the philosophy of religion to develop specific attention to the structure of religious experience and its common characteristics in all religions. In this way, the philosophy of religion also presents itself as a generator of interreligious dialogue and, therefore, capable of defusing the rise of fundamentalist violence.
Keywords: religion; philosophy; spain; latin america; hermeneutics